Theatricalization of self : personal blogs as theatre performance - Siler, Martina (2012)
The aim of this thesis is to compare personal blogs and theatre art. The study is conducted as theoretical discourse and focuses on comparison of personal blogs with a subgenre of theatre art, performance art. Using actual selected examples from theatre art as well as from personal blogs, the study aims to outline the similarities, which personal blogs share with theatre performance. The theoretical framework of the thesis suggests that personal blogs with their nature of the observed subject, the blogger, and the observer, the reader, produce one of the basic elements of theatre art, theatricality. Furthermore, personal blogs are placed closer to postdramatic theatre, a form of theatre art that denies Western theatrical tradition and explores theatrical expression in many different ways. One of the genres of postdramatic theatre is also autobiographical performance. The theatre art of personal blogs equals this specific category of performance, where the performer tells her or his personal story in front of the audience. Both autobiographical performance and a personal blog tell about the performer’s (the blogger’s) self and about various aspects of her or his life. Since personal blogs reside within their own media, which is far from actual theatre art, the idea of autobiographical performance in personal blogs is approached with Bolter and Grusin’s concept of remediation. Additionally, the thesis includes Brenda Laurel’s proposal that computers share their nature with theatre art and thus also remediate theatre. In addition, the thesis examines the role of the personal blog’s reader, the spectator, suggesting that there are at least three different categories of the personal blog’s audience. Finally, the thesis introduces some selected examples of actual theatre productions both in theatre and on the Internet (e.g. the series of projects Ballettikka Internettikka by Slovene artists Igor Štromajer and Brane Zorman) to get a better insight into the performative nature of personal blogging.